Peer-reviewed active learning engagement with a multi-level remedial class - Alwani Omar, Nor; Suraya Sarudin, Ezzah; Mohd Nasir, Arfah; Masrom, Suraya; Ahmad, Norhasliza (International Journal of Engineering and Technology, 2018)
This study was conducted to find the effectiveness of the remedial class to the studentsâ€™ performance in Mathematical courses. Two objectives were highlight which are the active learning engagement among participants and the effectiveness of the remedial class. The respondents of this study is 169 semester one students of Diploma in Sciences. All students were involved in the first remedial class and the result of the students later was compared with the previous semester. The result shows there is improvement in studentsâ€™ performance as the failure rate for that semester is lower compared to the previous one. Next, students who passed in Pre-calculus was divided into two groups for the next semester. The control group proceed with calculus I without second remedial class while the experimental group need to attend second remedial class. The result of these students in Calculus I later was collected and analyzed. The statistics shows there is slight improvement in failure rate for experimental group. Thus, it shows that multi-level remedial class is a new effective approach to improve studentsâ€™ poor foundation in Mathematics. Besides, it is indirectly beneficial to the faculty and university as there will be less students who do not graduate on time.Â Â